PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI BADAN LINGKUNGAN HIDUP (BLH) KOTA PROBOLINGGO - Yayuk Indah Wahyuning Tyas; Ngatimun .; Tri Bangkit Sutrisno (UNEJ e-Proceeding)
This research aimed to know how much influence of the leadership style and work motivation on employee satisfaction Environmental Agency Kota Probolinggo. This type of research is descriptive with causal associative approach the research done by the outline descriptive question the relationship between two or more variables that diteliti. This research was conducted with the number of respondents was 60 orang. Data collection method data in this study is a preliminary survey, literature study and survey lapangan.Teknik sampling sampling techniques used are saturated. Hypothesis testing is done by multiple linear regression analysis for hypotheses by SPSS 22 for windows. Based on the test results of t test (partial) obtained Leadership Style variables significantly influence Job Satisfaction Motivation Kerja.Sedangkan on job satisfaction obtained thitung≤ ttabel (0,952≤ 2.002) it means that the work motivation variable no significant effect on job satisfaction. While the test results F test (simultaneous) significance value of F> F table (10.187> 3.16) H0 is rejected it means simultaneously leadership style and work motivation significant effect on job satisfaction.